Love, learning, and identity at New Hope: a critical ethnographic study of how young coloured men construct and perform race, masculinity, and sexuality at a Northern Cape High School - Makhetha, Trevor (Stellenbosch : Stellenbosch University, 2025)
Thesis (PhD)--Stellenbosch University, 2025.